1969
DOI: 10.1021/ja01038a012
|View full text |Cite
|
Sign up to set email alerts
|

Photodecarboxylation of nitrophenylacetate ions

Abstract: These studies characterize the primary process and products in the photodecarboxylation of nitrophenylacetate ions in aqueous solutions. 3-Nitrophenylacetate, 4-nitrophenylacetate, and 4-nitrohomophthalate ions decarboxylate with a quantum yield of about 0.6 at 367 nm, while that of o-nitro structures (2-nitrophenylacetate and 2,4-dinitrophenylacetate ions) is only 0.04. acz'-Nitro intermediates are identified spectrally by flash photolyses from the o-and p-nitro structures, but not from the m-nitro structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 0 publications
2
51
1
Order By: Relevance
“…[21] Nitrophenylacetates (NPAs) utilize a similar photodecarboxylation mechanism, but require UV light to initiate the uncaging chemistry. [22][23][24] Although both oNB and NPAs contain nitrobenzyl groups, NPA decarboxylation does not involve the hydrogen atom abstraction utilized in oNB uncaging. Despite the potential advantages, this type of decarboxylation process has not been applied to metal ion photocages.…”
mentioning
confidence: 99%
“…[21] Nitrophenylacetates (NPAs) utilize a similar photodecarboxylation mechanism, but require UV light to initiate the uncaging chemistry. [22][23][24] Although both oNB and NPAs contain nitrobenzyl groups, NPA decarboxylation does not involve the hydrogen atom abstraction utilized in oNB uncaging. Despite the potential advantages, this type of decarboxylation process has not been applied to metal ion photocages.…”
mentioning
confidence: 99%
“…[4] ortho-NPA (o-NPA) exhibits a quantum yield of only 4 % with respect to CO 2 release, whereas meta-and para-NPA have quantum yields of 63 % and 59 %, respectively. [5] For p-NPA, the first reaction intermediate has been assigned to a triplet species, being responsible for CO 2 release. [6] This is supported by efficient intersystem crossing (ISC) of nitrobenzylic compounds in general, with triplet rise times of 5-10 ps and yields of 60-80 %.…”
mentioning
confidence: 99%
“…Mass spectra and 1 H and 13 C NMR spectra confirmed the structures of the products. The mass spectral analysis of 18 O-mNPAA showed that 18 O-labeling was not complete, most likely due to exposure of the substance to acidic aqueous conditions during the final extraction. It is known that in aqueous solutions carboxylic acids exchange carbonyl oxygen atoms with the solvent.…”
Section: Synthesis Of Derivativesmentioning
confidence: 99%
“…was then added, and the now brownish suspension was filtered. The filtrate was washed with water (2 50 cm 3 ), dried (MgSO 4 ), and concentrated under reduced pressure to yield a brownish oil, which was fractionally distilled in vacuo to afford product 3 (4.4 g, 48 %) as a yellowish oil, containing [18]crown-6 (6 %). ) in a screw-cap vial was exposed to a stream of gaseous HCl for 2 h until the solution solidified.…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation